Maximum torque per ampere control of permanent magnet/reluctance hybrid rotor dual stator synchronous motor - Shi Jin; Wuhen Jin; Hao Wang; Siyang Yu; Zhaoyu Zhang (IET Electric Power Applications, 2024)
Abstract Compared with a traditional low‐speed high‐torque permanent magnet synchronous motor (PMSM), a permanent magnet (PM)/reluctance hybrid rotor dual‐stator synchronous motor (PM/RHRDSSM) has the advantages of high torque density and high space utilization. This type of motor is composed of a "back‐to‐back" PM + reluctance hybrid rotor and an inner and outer double stator. The number of poles of the inner and outer unit motors is the same, and the inner and outer stator windings are connected in series, driven by a single inverter. Due to the special mechanical structure and electromagnetic relationship of PM/RHRDSSM, traditional PMSM and synchronous reluctance motor maximum torque per ampere (MTPA) control strategies are no longer applicable. In response to this issue, the authors establishe a PM/RHRDSSM mathematical model of stator winding series structure and propose a MTPA control strategy suitable for this new type of motor. This strategy is aimed at the special mathematical model of PM/RHRDSSM and derives the analytical expression of MTPA trajectory, which minimises the required stator current amplitude of PM/RHRDSSM at various load torques, thereby minimising the motor copper loss. Finally, the effectiveness and practicality of the proposed control strategy were verified through simulation and experiments.